2017
DOI: 10.1038/s41467-017-01845-1
|View full text |Cite
|
Sign up to set email alerts
|

Notch transactivates Rheb to maintain the multipotency of TSC-null cells

Abstract: Differentiation abnormalities are a hallmark of tuberous sclerosis complex (TSC) manifestations; however, the genesis of these abnormalities remains unclear. Here we report on mechanisms controlling the multi-lineage, early neuronal progenitor and neural stem-like cell characteristics of lymphangioleiomyomatosis (LAM) and angiomyolipoma cells. These mechanisms include the activation of a previously unreported Rheb-Notch-Rheb regulatory loop, in which the cyclic binding of Notch1 to the Notch-responsive element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 66 publications
(92 reference statements)
2
20
0
Order By: Relevance
“…This reprogramming is capable of maintaining a rapamycin non-responsive (resistant) cell population within the TSC/LAM lesions. Stemness markers have been previously identified in TSC-related cell models and involve the interplay between Notch and Rheb 69 . Interestingly, we found that expression of Dvl1 (Disheveled), an inhibitor of Notch signaling, was up-regulated in rapamycin-treated ELT3-245, compared to rapamycin-treated ELT3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This reprogramming is capable of maintaining a rapamycin non-responsive (resistant) cell population within the TSC/LAM lesions. Stemness markers have been previously identified in TSC-related cell models and involve the interplay between Notch and Rheb 69 . Interestingly, we found that expression of Dvl1 (Disheveled), an inhibitor of Notch signaling, was up-regulated in rapamycin-treated ELT3-245, compared to rapamycin-treated ELT3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations lead to the conclusion that CD133+CD24+ renal epithelial cells may represent a multipotent stem cell population. The recent observations that amgiomyolipomas in tuberous sclerosis derive from a multipotent cancer stem cell that originate from renal epithelium confirmed the hypothesis that the renal epithelium may have differentiation capacity that goes beyond the epithelial phenotype, which was considered to be its only possible lineage based on lineage-tracing experiments performed in mouse models of AKI [96][97][98]. Consistently, CD133+CD24+ renal epithelial cells exhibit cellular plasticity and stem-like properties, such as multipotency [92,95].…”
Section: Alternative Options For Kidney Regeneration: Renal Progenitomentioning
confidence: 70%
“…Recently, two studies suggested that angiomyolipomas originate from multipotent kidney epithelial cells localized in the tubule and undergoing clonal expansion in response to tuberous sclerosis complex (TSC) gene deletion [ 109 , 110 ]. Both studies proposed these cells could be renal progenitors with multilineage differentiation capacity [ 109 , 110 ].…”
Section: Tubular Progenitorsmentioning
confidence: 99%
“…Recently, two studies suggested that angiomyolipomas originate from multipotent kidney epithelial cells localized in the tubule and undergoing clonal expansion in response to tuberous sclerosis complex (TSC) gene deletion [ 109 , 110 ]. Both studies proposed these cells could be renal progenitors with multilineage differentiation capacity [ 109 , 110 ]. Interestingly, Cho et al revealed that the activation of a previously unreported Rheb-Notch-Rheb regulatory loop, in which the cyclic binding of Notch1 to the Notch-responsive elements (NREs) on the Rheb promoter is a key event, was the main mechanism behind the generation of the multiple lineages present in angiomyolipoma [ 109 ].…”
Section: Tubular Progenitorsmentioning
confidence: 99%